A perfect fit: Bacteriophage receptor-binding proteins for diagnostic and therapeutic applications. (February 2023) - Klumpp, Jochen; Dunne, Matthew; Loessner, Martin J
Abstract : Bacteriophages are the most abundant biological entity on earth, acting as the predators and evolutionary drivers of bacteria. Owing to their inherent ability to specifically infect and kill bacteria, phages and their encoded endolysins and receptor-binding proteins (RBPs) have enormous potential for development into precision antimicrobials for treatment of bacterial infections and microbial disbalances; or as biocontrol agents to tackle bacterial contaminations during various biotechnological processes. The extraordinary binding specificity of phages and RBPs can be exploited in various areas of bacterial diagnostics and monitoring, from food production to health care. We review and describe the distinctive features of phage RBPs, explain why they are attractive candidates for use as therapeutics and in diagnostics, discuss recent applications using RBPs, and finally provide our perspective on how synthetic technology and artificial intelligence-driven approaches will revolutionize how we use these tools in the future.